Agrobacterium-mediated transformation of rice the salt tolerance gene TaNHX1 (Experimental biology, 2015)
The rice variety Bakanas was co-transformed with the salt tolerance gene TaNHX1 and the HPT selective marker gene using Agrobacterium-mediated transformation. Salt-tolerant transgenic plants were obtained. The resulting salt-tolerant transgenic plants were tested by PCR analysis using Actin 1 promoter forward primer and NosTr reverse primer.
Keywords: rice; agrotransformation; salt tolerance; gen; regenerant